Obsesi Tokoh Nenek Dalam Gamitan Biososiokultural pada Novel Nenek Hebat Dari Saga Karya Yoshici Shimada - Erni, Erni; Piliang, Wilda Srihastuty Handayani (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
The problem of natural disasters is a form of human inability to understand environmental ethics. Humans cause the tendency for natural disasters to occur. Humans, as creatures equipped with thoughts and are believed to be leaders, still violate the provisions that apply in tradition. This study aims to reveal the obsession and idealistic manifestation of women in the